Community Pharmacists' Opinions on Nutritional Counseling for Oral Nutritional Supplements: An Exploratory Qualitative Study: Exploring Community Pharmacists' Role in Nutritional Counseling for Oral Nutritional Supplements (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The effects of malnutrition on the body are more severe in the elderly. Malnourished peoplemay benefit greatly from the use of oral nutritional supplements (ONS). Community pharmacies oftenstock many ONS, giving pharmacists more options when developing plans to curb the prevalenceof and keep an eye on patients' malnutrition. The researchers set out to learn how communitypharmacists deal with counseling and following up with ONS users. Interviews were conducted with16 pharmacists representing 19 community pharmacies.